Corrosion behaviour of substoichiometric TiNx films produced by DC magnetron sputtering - Ariza, E. (2003)
The present work describes the corrosion behaviour of substoichiometric TiNx films obtained by dc reactive magnetron sputtering. The coatings thickness ranged from 1.7 to 4.2 µm and the nitrogen content varied between 0 and 55 at. %. According to structural characterization by XRD, the films revealed a hexagonal α-Ti phase with a strong [002] orientation for low nitrogen contents. For nitrogen contents of 20% and 30%, the ε-Ti2N phase appears with a [200] orientation and further increasing of nitrogen content showed that the δ-TiN phase was dominant. Potentiodynamic polarisation and Electrochemical Impedance Spectroscopy (EIS) techniques were used to study the corrosion properties of TiNx films when immersed in artificial sweat solutions. Results of potentiodynamic polarisation tests showed that all films have a high corrosion resistance reflected by corrosion current densities values lower than 0.7µA/cm2. Also, EIS tests corroborated the results obtained in the polarisation tests, showing that films containing low percentages of nitrogen (less than 8 %) reveal the best corrosion resistance. Further increases in nitrogen content lead to a decrease in corrosion resistance. An exception to this behaviour was found for the film, with 30 % N. This sample presents an excellent corrosion resistance which increases with the immersion time. Higher nitrogen contents (52 and 55 %) promote a relative increase in the corrosion resistance when compared with 45 and 50 at % films, but never reaching values obtained for nitrogen contents lower than 30 % at.